PATRIARKAL DAN FEMINIS PADA AYAT RELASI LAKI-LAKI DAN PEREMPUAN: (Studi Komparatif Penafsiran Al-Qur’an dan Al-Kitab) - Nor Kifli, Muhammad (JURNAL ILMIAH FALSAFAH: Jurnal Kajian Filsafat, Teologi dan Humaniora, 2021)
This article tries to discuss the position or relationship between men and women in Islam and Christianity. Departing from previous research that has not yet been carried out, there is no comparison regarding the relationship between men and women in Islam and Christianity. In fact, discussions on this theme do not only occur among Muslims but also among Christians. This study uses a literature study with primary data in the form of the holy book, namely the Qur'an with several interpretations of the scholars and also uses the Al-Kitab and secondary data is taken from the literature related to this topic. The results of this study indicate that the adherents of Islam and Christianity can be categorized into two groups in terms of reading the verses of the relationship between men and women. The first group is a group whose readings use a patriarchal approach. The interpretation in this patriarchal form is mostly done by men, so that in the interpretation products they are more likely to prioritize their needs as a man, without looking at the actual needs of a woman so that it seems discriminatory. The second is the group whose readings use a feminist approach. This interpretation with a feminist approach is actually a response to a patriarchal interpretation that tends to exclude, discriminate and dominate women. This group with a feminist approach tries to interpret and explain texts that seem hierarchical and conclude that basically men and women have the same position.